Peran Masyarakat Dalam Pelanggaran Hukum Konservasi Sumber Daya Alam Hayati dan Ekosistemnya oleh Aktivitas Pertambangan Pasir Besi di Desa Pasar Seluma - Mardhatillah, Mardhatillah; Putra, Handyka Pribowo (Innovative: Journal Of Social Science Research, 2024)
Pasar Seluma is located on the west coast of Bengkulu province and has a protected forest area that has been maintained for a long time. Being in a strategic position, it gives the community the opportunity to manage natural resources, especially those from the coast. However, this became complicated when the company PT Faminglevto Bakti Abadi entered in 1973 to carry out iron sand mining activities on the coast of the village. The Pasar Seluma Nature Reserve is located on the coast of Seluma district, a disaster-prone area that can actually function as a 'natural living fence'.According to the Law on Conservation of Living Natural Resources and Ecosystems, protecting these areas is the responsibility and obligation of both the government and the community. In this case, amidst environmental problems and regulatory inconsistencies, the people of Pasar Seluma carried out various activities with the aim of rejecting PT.FBA's operations to defend the existing conservation area. This research uses an empirical legal research method that involves searching and collecting data collectively through site observations and interviews with respondents as well as a case approach. This research will examine the role of the local community, namely the Pasar Seluma Village Community, in efforts to defend the nature reserve area from mining activities that have the potential to damage the environment and how legal violations committed by PT Faminglevto Bakti Abadi.